Retinal astrocyte morphology predicts integration of vascular and neuronal architecture - Holden, Joseph M.; Wareham, Lauren K.; Calkins, David J. (Frontiers in Neuroscience, 2023)
Astrocytes are important regulators of blood flow and play a key role in the response to injury and disease in the central nervous system (CNS). Despite having an understanding that structural changes to these cells have consequences for local neurovascular physiology, individual astrocyte morphology remains largely unexplored in the retina. Here, we used MORF3 mice to capture full membranous morphology for over fifteen hundred individual astrocytes in the mouse retina, a highly metabolically active component of the CNS. We demonstrate that retinal astrocytes have been misrepresented as stellate in morphology due to marker use like GFAP and S100β which underestimates cell complexity. We also find that astrocytes contain recurring morphological motifs which are predictive of the underlying neurovascular architecture of the inner retina and suggestive of function. These motifs predict fine sampling and integration of retinal ganglion cell electrical activity with consequences for blood flow regulation. Additionally, our data shows that astrocytes participate in neurovascular interactions to a much greater degree than currently reported. 100% of cells contact the vasculature through one of three mutually exclusive classes of connections. Similarly, 100% of cells contact some neuronal element, be it an RGC axon or soma. Finally, we report that astrocyte morphology depends on retinal eccentricity, with cells appearing compressed near the nerve head and in the periphery. These results reveal a large degree of astrocyte morphological complexity that informs their contribution to neurovascular coupling in the retina.